Real time Analysis of unstained Human Sperm Head Morphology Using Texture Based Image Processing (International Journal of Food and Nutritional Sciences, 2022)
About 15-20% couple seek medical advice for difficulty in conceiving, of which nearly 40% require Intra Cytoplasmic Sperm Injection (ICSI) to aid in getting pregnant by assisted reproductive technologies. Semen examination especially morphometric assessment is done to assess and assist the couple but, its done on stained smear of semen from male partner in a diagnostic set up, on the day of procedure morphologically normal sperm is chosen by the embryologist under lower powered optics in an unstained preparation of motile sperms leading to subjectivity. In this paper we developed a realtime computer assisted sperm head morphology analyzer to objectively select morphometrically normal sperm in unstained live specimen using IMAGEJ (Image Processing using JAVA) open source tool.